How industry collaboration influences research: The case of the Swedish interdisciplinary materials consortia, 1990–2000. Issue 5 (October 2019) - Perez Vico, Eugenia; Hallonsten, Olof
This article provides new insights into the consequences of university–industry collaboration for the content and conduct of academic research by analysing the Swedish research funding programme for the so-called 'materials consortia', in place between 1990 and 2000. Using secondary sources, the analysis highlights the causality in university–industry collaboration and the impact of such collaboration on the academic research environments involved. While the funding programme was clearly aimed at influencing the conduct of academic research, impacts are seen mostly in content. Also, collaborative activities with long-term positive outcomes grew organically rather than top-down, with mutual trust and recognition at the operational level of great importance. The policy implications include the realization that the durability of efforts, from funders as well as at the operational level, is key to achieving deeper added value in university–industry collaborations. The article contributes to a deepened and broadened understanding of the multidimensionality of university–industry collaborations and their effects on research.